PERAN E-COMMERCE DAN KAPABILITAS INOVASI DALAM MEMPENGARUHI KINERJA UMKM DI KABUPATEN SUMBAWA - Handayani, Silva; Fietroh, Muhammad Nur (Jurnal Ekonomi & Bisnis, 2024)
This study aims to examine the influence of e-commerce (X1) and innovation capability (X2) on the performance of MSMEs in Sumbawa District. The population in this study are MSME owners in Sumbawa District, the exact number of which is not known. Seeing that the research population is very large and the researcher does not know the exact number, to determine the sample size for this study, Paul Leedy's formula was used to obtain a sample size of 100 people who would be used as research respondents. In this study, information was collected through questionnaires given to respondents. The data that has been collected will then be processed using the SPSS program to be studied using analytical techniques, including multiple linear regression analysis, partial hypothesis testing (t test), and determinant coefficient test (R2). The results of this study showed that the e-commerce and innovation capability partially had a positive and significant effect on the performance of MSMEs in Sumbawa District. The influence of e-commerce variables and innovation capability on MSMEs performance variables in Sumbawa District is 53.6%, while the remaining 46.4% is influenced by other variables outside this research model, such as MSME actors' competency factors, marketing creativity, and access to capital.